2019
DOI: 10.1093/rheumatology/kez419
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study of obstetric antiphospholipid syndrome (OAPS) and non-criteria obstetric APS (NC-OAPS): report of 1640 cases from the EUROAPS registry

Abstract: Objectives To compare clinical features, laboratory data and fetal-maternal outcomes between 1000 women with obstetric APS (OAPS) and 640 with aPL-related obstetric complications not fulfilling Sydney criteria (non-criteria OAPS, NC-OAPS). Methods This was a retrospective and prospective multicentre study from the European Registry on Obstetric Antiphospholipid Syndrome. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 30 publications
6
99
1
1
Order By: Relevance
“…showed that in 1640 obstetric patients testing positive for aPL, those meeting and not meeting the Sydney criteria had similar treatment outcomes. 8 We likewise did not find a statistically significant difference in response in patients meeting and not meeting Sydney criteria, including those with only non-criteria aPL.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…showed that in 1640 obstetric patients testing positive for aPL, those meeting and not meeting the Sydney criteria had similar treatment outcomes. 8 We likewise did not find a statistically significant difference in response in patients meeting and not meeting Sydney criteria, including those with only non-criteria aPL.…”
Section: Discussionmentioning
confidence: 46%
“…“Criteria” aPL include anticardiolipin and anti-beta-2 glycoprotein-1 antibodies and the lupus anticoagulant. There are also “non-criteria” aPL 7,8 and “non-criteria” clinical manifestations which span every specialty of medicine. 49…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line with the recommendations of the European League against Rheumatism (EULAR) regarding prevention of obstetric APS, 17 and may indicate the need for active management of APS that does not completely meet the diagnostic criteria in women with SLE. 18–20…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the recommendations of the European League against Rheumatism (EULAR) regarding prevention of obstetric APS, 17 and may indicate the need for active management of APS that does not completely meet the diagnostic criteria in women with SLE. [18][19][20] We found that the rate of pregnancy loss (encompassing early fetal loss and stillbirth) was high among women with SLE onset during pregnancy. In contrast to pregnant women with pre-existing SLE, none of the factors we analyzed were associated with pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…22 The vascular endothelium is therefore a major target of novel therapies to disrupt pathogen attachment in an attempt to slow or stop progression of sepsis to a life-threatening situation. For references see Miyakis et al, 24 Alijotis-Reig et al, 25…”
Section: Vascular Endothelial Cell Dysregulation During Sepsis Steve mentioning
confidence: 99%